2009
DOI: 10.1088/0004-637x/700/2/931
|View full text |Cite
|
Sign up to set email alerts
|

On the Heating Efficiency Derived From Observations of Young Super Star Clusters in M82

Abstract: Here, we discuss the mechanical feedback that massive stellar clusters provide to the interstellar medium of their host galaxy. We apply an analytic theory developed in a previous study for M82-A1 to a sample of 10 clusters located in the central zone of the starburst galaxy M82, all surrounded by compact and dense H ii regions. We claim that the only way that such H ii regions can survive around the selected clusters, is if they are embedded into a high-pressure ISM and if the majority of their mechanical ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…We found that massive clusters, like NGC 604 and NGC 595, should exhibit NIR-MIR excesses during a significant fraction of their evolution, especially if the heating efficiency of the thermalized matter is low as suggested by several independent studies (e.g. Smith et al 2006;Silich et al 2009). With regard to star clusters with masses of a few times ∼ 10 4 M ⊙ , we propose that the evolutionary trends of the NIR-MIR emission obtained from our models is well represented by NGC 592, NGC 592, IC 131 and IC 131-West, which have similar masses and their emission at wavelengths ≥ 10 µm is almost identical.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We found that massive clusters, like NGC 604 and NGC 595, should exhibit NIR-MIR excesses during a significant fraction of their evolution, especially if the heating efficiency of the thermalized matter is low as suggested by several independent studies (e.g. Smith et al 2006;Silich et al 2009). With regard to star clusters with masses of a few times ∼ 10 4 M ⊙ , we propose that the evolutionary trends of the NIR-MIR emission obtained from our models is well represented by NGC 592, NGC 592, IC 131 and IC 131-West, which have similar masses and their emission at wavelengths ≥ 10 µm is almost identical.…”
Section: Discussionsupporting
confidence: 54%
“…4. A low efficiency in the thermalization of the kinetic energy of stellar winds and supernova explosions (Silich et al 2007(Silich et al , 2009) would also alleviate the destruction of grains of all sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial parameter determining where the 2G stars form is the heating efficiency: if it is low (of order 1−10%), 2G stars form only in the center; if it is larger, 2G stars form everywhere throughout the cluster (see regions "compact 2G" and "extended 2G" on the parameter space map in Figure 10). The heating efficiency is closely related to the temperature of the hot shocked wind within the cluster and there is some observational evidence, that it may indeed be low (Silich et al 2009;Rosen et al 2014). This is interesting in terms of the aforementioned mass budget problem, because if 1G and 2G stars are spatially separated in this way, a substantial fraction of 1G stars can be lost due to the primordial gas expulsion and the subsequent dynamical evolution (Khalaj & Baumgardt 2016).…”
Section: Discussionmentioning
confidence: 94%
“…The large central temperature depressions at the critical line and the slow acceleration of the reinserted matter within the cluster are indicative of the last stationary solution found before crossing the critical line. The presence of dust in the thermalized plasma within young SSCs provides a natural explanation for the observational and theoretical studies that have derived a strongly reduced mechanical energy output from some of the massive clusters in the galaxy M82 in order to account for the size of the compact H ii regions that surround them (see Smith et al 2006;Silich et al 2007Silich et al , 2009. Further evidence for the bimodal solution and the positive star formation feedback may come from the interpretation of the abundance variations from star to star in massive globular clusters (GC), such as ω Cen in the Milky Way where different generations of stars are enriched by different contributors, and among these by core-collapse SNe (Gratton et al 2004) or from observations of the most massive GCs in M31 where the run of α to Fe-peak elements is consistent with a primordial enrichment from stars with masses larger than 10 M (Meylan et al 2001).…”
Section: Strong Radiative Cooling and The Location Of The Threshold Linementioning
confidence: 99%